A comparative study on gunpowder erosion and promoted ignition combustion of 30SiMn2MoV gun barrel. (December 2022) - Dou, Caihong; Su, Bo; Wang, Congzhen; Jin, Pengfei; Chen, Junyu; Huang, Jinfeng; Zhang, Cheng
Highlights: Erosion pits and micro-cracks were both composed of sulfides, oxides and molten phases. The molten oxides zone with an amorphous structure was observed in the erosion pits and a similar molten microstructure was also observed along the grain boundaries of oxides in the propagating eroded cracks. Erosion pits consisting of oxides and eutectic microstructure were observed on the surface of 30SiMn2MoV gun barrel steel after promoted ignition combustion test. A mechanism of erosion products based on the view of micro-combustion was proposed by comparing microstructure, thermodynamic, and kinetic characteristics. Abstract: Various failure mechanisms of gun barrel based on thermal or thermochemical coupling have been proposed, but the understanding of microstructure evolution in the erosion process is still restricted. In this paper, the microstructure of a 30SiMn2MoV gun barrel after gunpowder erosion was investigated and compared with that after promoted ignition combustion test. In the failed barrel, erosion pits and micro-cracks were observed at the beginning of rifling. TEM and EDS analysis showed that erosion pits and micro-cracks were both composed of sulfides, oxides, and molten phases. Molten oxide zone with amorphous structure was observed in the erosion pits and similar molten microstructure was also observed along the grain boundaries of oxide in the propagating eroded cracks. Erosion pits consisting of oxides and eutectic microstructure were observed on the surface of 30SiMn2MoV steel after combustion. By comparing of microstructure, thermodynamic and kinetic characteristics, a barrel erosion mechanism based on the view of micro-combustion was proposed.